2019
DOI: 10.1111/odi.13139
|View full text |Cite
|
Sign up to set email alerts
|

PAX7nucleotide variants and the risk of non‐syndromic orofacial clefts in the Polish population

Abstract: Objective The etiology of non‐syndromic cleft lip with or without cleft palate (nsCL/P) is multifactorial, heterogeneous, and still not completely understood. The aim of the present study was to examine the associations between common and rare PAX7 nucleotide variants and the risk of this common congenital anomaly in a Polish population. Subjects and methods Eight top nsCL/P‐associated PAX7 variants identified in our cleft genome‐wide association study (GWAS) were selected for replication analysis in an indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“… 57 , 58 Several SNPs have been reported to increase the risk of nonsyndromic CL/P. 59 , 60 Our finding thus supported the utilities of the DeepFace model; however, further experiment validation of the regulatory roles of these two SNPs will be warranted. We further discuss their roles below.…”
Section: Discussionsupporting
confidence: 72%
“… 57 , 58 Several SNPs have been reported to increase the risk of nonsyndromic CL/P. 59 , 60 Our finding thus supported the utilities of the DeepFace model; however, further experiment validation of the regulatory roles of these two SNPs will be warranted. We further discuss their roles below.…”
Section: Discussionsupporting
confidence: 72%
“…24 A multiethnic genome-wide meta-analysis of the rs9439714 showed a significant association with nonsyndromic orofacial clefts. 32,33 The rs1339062 was strongly associated with NSCL/P (p-value ¼ 2.47E À 05, OR ¼ 1.4) in the Polish population, 34 whereas in an Asian and European trio, the SNP rs1339062 showed no significance. 35 Guo et al found no significance for rs6695765 and rs742071 in a case-control study on nonsyndromic orofacial clefts from northern China.…”
Section: Discussionmentioning
confidence: 97%
“…In humans, SNPs or mutations in the FGFR1 gene are associated with non-syndromic CL/P ( 84 , 85 ). PAX7, a TF containing a paired box domain, an octapeptide, and a paired-type homeodomain, plays roles in craniofacial development ( 86 ), and PAX7 nucleotide variants are associated with non-syndromic CL/P ( 87 ). SUMO1, an ubiquitin-like protein, plays roles in various cellular processes, such as nuclear transport, transcriptional regulation, and apoptosis, through sumoylation of many genes.…”
Section: Discussionmentioning
confidence: 99%